Stable oxyntomodulin analogues exert positive effects on hippocampal neurogenesis and gene expression as well as improving glucose homeostasis in high fat fed mice. (5th September 2015) - Pathak, N.M.; Pathak, V.; Lynch, A.M.; Irwin, N.; Gault, V.A.; Flatt, P.R.
Highlights: (d S 2 )Oxm[K-γ-glu-Pal] and (d S 2 )Oxm enhanced hippocampal neurogenesis. Both Oxm peptides improved hippocampal synaptophysin staining. Hippocampus and cortex were protected from oxidative stress by Oxm peptides. Hippocampal mRNA expression of MASH1, SIRT1, GLUT4 and IRS1 was up-regulated. Beneficial effects on brain function were accompanied by improved metabolic control. Abstract: The weight-lowering and gluco-regulatory actions of oxyntomodulin (Oxm) have been well-documented however potential actions of this peptide in brain regions associated with learning and memory have not yet been evaluated. The present study examined the long-term actions of a stable acylated analogue of Oxm, (d S 2 )Oxm(K-γ-glu-Pal), together with parent (d S 2 )Oxm peptide, on hippocampal neurogenesis, gene expression and metabolic control in high fat (HF) mice. Groups of HF mice (n = 12) received twice-daily injections of Oxm analogues (both at 25 nmol/kg body weight) or saline vehicle (0.9% wt/vol) over 28 days. Hippocampal gene expression and histology were assessed together with evaluation of energy intake, body weight, non-fasting glucose and insulin, glucose tolerance, insulin sensitivity and lipids. Oxm analogues significantly reduced body weight, improved glucose tolerance, glucose-mediated insulin secretion, insulin sensitivity, islet architecture and lipid profile. Analysis of brain histology revealed significant reduction in hippocampal oxidative damage (8-oxoguanine), enhanced hippocampal neurogenesis (doublecortin) and improved hippocampal and cortical synaptogenesis (synaptophysin) following treatment. Furthermore, Oxm analogues up-regulated hippocampal mRNA expression of MASH1, Synaptophysin, SIRT1, GLUT4 and IRS1, and down-regulated expression of LDL-R and GSK3β. These data demonstrate potential of stable Oxm analogues, and particularly (d S 2 )Oxm(K-γ-glu-Pal) to improve metabolic function and enhance neurogenesis, synaptic plasticity, insulin signalling and exert protective effects against oxidative damage in hippocampus and cortex brain regions in HF mice.